The Consequence of Human Resource Planning on Organizational Performance: An Ephemeral Review - Hasan Elsan Mansaray (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2019)
The drive for human resource planning in every single organization is to necessitate perfect use of human resource currently employed as well as, making provision for the future human resource needs regarding skills, quantities and ages. The purpose of this review is to ascertain the practices of HRP that can increase organizational performance. Consequently, the review discovered that HR planning ensures that organizations at all times have the right number of people, with the correct level of skills to do the right activities at the right time for the achievement of organizational objectives. Besides, human resource planning determines the right numerical strength of individuals that own these skills that are needed by organisations to meet the present and future business requirements. Based on this reality, organisations nowadays need to have employees that possess the right skills that could be place in the right places and at the right time they would be needed in organizations. In order to fulfill this condition, the study found out that HR planning ought to be part of any organization’s objective. Incredibly, many organizations have the tendency of overlooking the side of HR planning and more or less, organizations are even not totally conscious of it. Hence, it is essential to recognize that because of the high knowledge requirements in the global market, most organizations are determine to stimulate performance, which can engender surplus profit through the application of HRP philosophy.